Temporal evolution of gamma activity in human cortex during an overt and covert word repetition task - Leuthardt, Eric; Pei, Xiao-mei; Breshears, Jonathan; Gaona, Charles; Sharma, Mohit; Freudenburg, Zachary; Barbour, Dennis; Schalk, Gerwin (Frontiers in Human Neuroscience, 2012)
Different models for cortical processing of speech have been proposed. Classically, the regions participating in language were thought to be modular with a linear sequence of activations. More recently, modern theoretical models have posited a more hierarchical and distributed interaction of anatomic areas for the various stages of speech processing. Traditional imaging techniques can only define the location or time of cortical activation, which impedes the further validation and refinement of these models. In this study, we take advantage of recordings from the surface of the brain (electrocorticography ECoG)), which can accurately detect the location and timing of cortical activations, to study the time course of ECoG gamma modulations during an overt and covert word repetition task for different cortical areas. For overt word production, our results show substantial perisylvian cortical activations early in the perceptual phase of the task that were maintained through word articulation. However, this broad activation is attenuated during the expressive phase of covert word repetition. Across the different repetition tasks, the utilization of the different cortical sites within the perisylvian region varied dependent on which stimulus was provided (auditory or visual cue) and whether the word was to be spoken or imagined. Taken together, the data supports current models of speech that were defined with functional imaging. Moreover, this study demonstrates that the broad perisylvian speech network variably utilizes these cortical resources based on the nature of the cognitive task.